Relationship between Organizational Culture and Locus of Control with Bogor Regency Employee Performance - Saprudin, Saprudin; Rosyaty, Tuty; Syukron, Ahmad (International Review of Management and Marketing, 2019)
This study aims to determine the relationship between Organizational Culture and Locus of Control with the Performance of Bogor Regency Employees. The method used is a survey with a correlational study involving 112 sample people. There are three instruments that measure performance (rel. 936), organizational culture (rail. 790), and locus of control (rel. 912). Data has been analyzed by two-way ANOVA. The results revealed that there were positive and significant correlations between these variables, even though they were controlled by second-order correlations, still significant between them. Therefore it can be concluded that if the performance will be improved, the Organizational Culture and Locus of Control employees must be considered. Keywords: performance, organizational culture, locus of control JEL Classifications: L2, M14 DOI: https://doi.org/10.32479/irmm.8171